The Neurocognitive Performance of Visuospatial Attention in Children with Obesity - Tsai, Chia-Liang; Chen, Fu-Chen; Pan, Chien-Yu; Tseng, Yu-Ting (Frontiers in Psychology, 2016)
The present study investigates the behavioral performance and event-related potentials (ERPs) in children with obesity and healthy weight children when performing a visuospatial attention task. Twenty-six children with obesity (obese group) and 26 healthy weight children (control group) were recruited. Their behavioral performance during a variant of the Posner paradigm was measured, and brain ERPs were recorded concurrently. The behavioral data revealed that the obese group responded more slowly, especially in the invalid condition, and exhibited a deficit in attentional inhibition capacity as compared to the control group. In terms of cognitive electrophysiological performance, although the obese group did not show significant differences on P3 latency elicited by the target stimuli when compared to the control group, they exhibited smaller P3 amplitudes when performing the visuospatial attention task. These results broaden previous findings, and indicate that childhood obesity is associated with a reduced ability to modulate the executive function network which supports visuospatial attention.